Expected small left heart size in the presence of congenital diaphragmatic hernia: Fetal values and Z-scores for infants confirmed to have no heart disease postnatally - Moon-Grady, Anita J.; Byrne, Francesca A.; Lusk, Leslie A.; Keller, Roberta L. (Frontiers in Pediatrics, 2022)
Objectives In fetuses with left-sided congenital diaphragmatic hernia (CDH), left heart structures may appear small, but usually normalize after birth in the absence of structural cardiac anomalies. To decrease the possibility of an erroneous diagnosis of structural heart disease, we identify normal values for left heart structures in the presence of left CDH and secondarily investigate the relationship of left heart size and survival to neonatal hospital discharge. Methods Left heart structures [mitral valve (MV) and aortic valve (AoV) annulus diameter, left ventricle (LV) length and width] were measured by fetal echocardiogram in fetuses with left CDH and no congenital heart disease. We generated linear regression models to establish the relationship of gestational age for each left heart structure using data from fetuses who survived after birth. We calculated z-scores (normalized to gestational age), and assessed the relationship of survival to the size of each structure. Results One hundred forty-two fetuses underwent fetal echocardiogram (median 25 weeks’ gestation, IQR 23, 27 weeks). Left heart structures were deemed small when using published normative data from unaffected fetuses (z-scores: MV -1.09±1.35, AoV -2.12±1.16, LV length -1.36±1.24, LV width -4.79±0.79). CDH-specific models derived from log-transformed values yielded right-shifted distributions, reflecting the small structures (mean z-score lower by: MV 0.99±0.30, AoV 2.04 ± 0.38, LV length 1.30±0.36, and LV width 4.69±0.28; p<0.0001 for all comparisons). Non-survivors had worse z-scores than survivors for all measurements, but this did not reach statistical significance. Conclusions Log-transformed linear models generated new normative data for fetal left heart structures in left CDH, which may be used to allay antenatal concerns regarding structural left heart anomalies. There were no significant differences in z-scores between survivors and non-survivors, suggesting that in the absence of true structural disease, cardiac evaluation is not predictive in isolation and that causes of mortality are likely multifactorial in this population.